2020
DOI: 10.3389/fmicb.2020.534692
|View full text |Cite
|
Sign up to set email alerts
|

Quorum-Sensing Regulator OpaR Directly Represses Seven Protease Genes in Vibrio parahaemolyticus

Abstract: Proteases play a key role in numerous bacterial physiological events. Microbial proteases are used in the pharmaceutical industry and in biomedical applications. The genus Vibrio comprises protease-producing bacteria. Proteases transform polypeptides into shorter chains for easier utilization. They also function as a virulence factor in pathogens. The mechanism by which protease genes are regulated in Vibrio parahaemolyticus, an emerging worldwide human pathogen, however, still remains unclear. Quorum sensing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 66 publications
2
11
1
Order By: Relevance
“…Similar to results of these researchers our findings showed that V. alginolyticus produced biofilm, pigment, elastase and amylase under the management QS. QS induced gene expression of Asp, protease from V. alginolyticus (Chang and Lee, 2020).Unlike the findings in study of Chang and Lee 2020, it was determined that V. alginolyticus no produce protease in our study.…”
Section: Discussioncontrasting
confidence: 96%
“…Similar to results of these researchers our findings showed that V. alginolyticus produced biofilm, pigment, elastase and amylase under the management QS. QS induced gene expression of Asp, protease from V. alginolyticus (Chang and Lee, 2020).Unlike the findings in study of Chang and Lee 2020, it was determined that V. alginolyticus no produce protease in our study.…”
Section: Discussioncontrasting
confidence: 96%
“…The gene expression level of the QS master regulator at a high cell density, OpaR, was found to be significantly downregulated in the furanone treatment ( Figure 7 ), but the suppression was not significant in the aptamer treatments. The role of OpaR in regulating QS has been frequently reported [ 73 , 74 , 75 ]. It is involved in biofilm formation, swarming, motility, and type-III and -VI secretion systems in V. parahaemolyticus [ 76 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Experiments were performed twice independently with three biological replicates each time. We used the raw data of the GEO datasets with the accession number GSE122479 generated in a previous report (36). The analysis was performed by the bioinformatic facility "Unidad de Análisis Bioinformáticos" from the Center for Genomic Sciences (UNAM).…”
Section: Luminescence Assaymentioning
confidence: 99%
“…It is possible that the change in c-di-GMP levels in the ΔopaR mutant strain under this condition is transient, while the resulting change in cpsA expression is more stable. As will be discussed later, OpaR is likely a direct regulator of cpsA expression and other biofilm related genes (23,35,36).…”
Section: Opar Is Capable Of Inhibiting Biofilm Formation and Cpsa Exp...mentioning
confidence: 99%